Comparison of neural histomorphology in tail tips from pigs docked using clippers or cautery iron. (1st December 2016) - Kells, N. J.; Beausoleil, N. J.; Johnson, C. B.; Sutherland, M. A.; Morrison, R. S.; Roe, W.
Abstract : Tail docking of pigs is commonly performed to reduce the incidence of unwanted tail-biting behaviour. Two docking methods are commonly used: blunt trauma cutting (i.e. using side clippers), or cutting and concurrent cauterisation using a hot cautery iron. A potential consequence of tail amputation is the development of neuromas at the docking site. Neuromas have been linked to neuropathic pain, which can influence the longer-term welfare of affected individuals. To determine whether method of tail docking influences the extent of neuroma formation, 75 pigs were allocated to one of three treatments at birth: tail docked using clippers; tail docked using cautery iron; tail left intact. Tail docking was performed at 2 days of age and pigs were kept under conventional conditions until slaughter at 21 weeks of age. Tails were removed following slaughter and subjected to histological examination. Nerve histomorphology was scored according to the following scale: 1=discrete well-organised nerve bundles; 2=moderate neural proliferation and disorganisation affecting more than half of the circumference of the tail; 3=marked neural proliferation to form almost continuous disorganised bundles or non-continuous enlarged bundles compressing the surrounding connective tissue. Scores of 2 or 3 indicated neuroma formation. Scores were higher in docked pigs than undocked pigs ( P <0.001), but did not differ between pigs docked using clippers and those docked using cautery ( P =0.23). The results indicate that tail docking using either clippers or cautery results in neuroma formation, thus having the potential to affect long-term pig welfare.